CARM1 regulates tubulin autoregulation through PI3KC2α R175 methylation - Yena Cho; Jee Won Hwang; Mark T. Bedford; Dae-Geun Song; Su-Nam Kim; Yong Kee Kim (Cell Communication and Signaling)
Abstract Tubulin is crucial in several cellular processes, including intracellular organization, organelle transport, motility, and chromosome segregation. Intracellular tubulin concentration is tightly regulated by an autoregulation mechanism, in which excess free tubulin promotes tubulin mRNA degradation. However, the details of how changes in free tubulin levels initiate this autoregulation remain unclear. In this study, we identified coactivator-associated arginine methyltransferase 1 (CARM1)-phosphatidylinositol 3-kinase class 2α (PI3KC2α) axis as a novel regulator of tubulin autoregulation. CARM1 stabilizes PI3KC2α by methylating its R175 residue. Once PI3KC2α is not methylated, it becomes unstable, leading to decreased cellular levels. Loss of PI3KC2α results in the release of tetratricopeptide repeat domain 5 (TTC5), which initiates tubulin autoregulation. Thus, PI3KC2α, along with its CARM1-mediated arginine methylation, regulates the initiation of tubulin autoregulation. Additionally, disruption of the CARM1-PI3KC2α axis decreases intracellular tubulin levels, leading to a synergistic increase in the cytotoxicity of microtubule-targeting agents (MTAs). Taken together, our study demonstrates that the CARM1-PI3KC2α axis is a key regulator of TTC5-mediated tubulin autoregulation and that disrupting this axis enhances the anti-cancer activity of MTAs.